Iron-catalyzed α-amidation of heterocycles with potential route to amino alcohols, amino thiols, and diamino products by nucleophilic ring opening. - Tania, Stefani. (2010)
An efficient method for α-amidation of heterocyclic moieties via direct nitrene insertion catalyzed by iron(III)trifluoromethanesulfonate with PhI=NTs (Ts = p-toluenesulfonyl)as a nitrogen source is reported herein. This reaction was shown to be applicable to cyclic ethers, cyclic thioethers, and pyrrolidines to afford the α-amino products in moderate to excellent yields. These amidated compounds were also shown to readily undergo nucleophilic ring opening to give amino alcohols, amino thiols, and diamino products in moderate to excellent yields.